2002
DOI: 10.1029/2001gl014298
|View full text |Cite
|
Sign up to set email alerts
|

Spaceborne measurements of atmospheric CO2 by high‐resolution NIR spectrometry of reflected sunlight: An introductory study

Abstract: .[1] We introduce a strategy for measuring the column-averaged CO 2 dry air volume mixing ratio X CO2 from space. It employs high resolution spectra of reflected sunlight taken simultaneously in near-infrared (NIR) CO 2 (1.58-mm and 2.06-mm) and O 2 (0.76-mm) bands. Simulation experiments, show that precisions of $0.3 -2.5 ppmv for X CO2 can be achieved from individual clear sky soundings for a range of atmospheric/surface conditions when the scattering optical depth t s is less than $0.3. When averaged over m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 10 publications
2
139
0
1
Order By: Relevance
“…8. These results corroborate the findings of Kuang et al (2002) using simulations. They also investigated the achievable XCO 2 precisions as a function of the total particle OD and found that, as OD increases from 0.05 to 0.25, the retrieval precision of XCO 2 over land only changes from ∼ 0.5 ppm (∼ 0.13 %) to ∼ 1.0 ppm (∼ 0.26 %).…”
Section: Influence Of Aerosols and Cloudssupporting
confidence: 90%
See 2 more Smart Citations
“…8. These results corroborate the findings of Kuang et al (2002) using simulations. They also investigated the achievable XCO 2 precisions as a function of the total particle OD and found that, as OD increases from 0.05 to 0.25, the retrieval precision of XCO 2 over land only changes from ∼ 0.5 ppm (∼ 0.13 %) to ∼ 1.0 ppm (∼ 0.26 %).…”
Section: Influence Of Aerosols and Cloudssupporting
confidence: 90%
“…For example, Kuang et al (2002) conducted an introductory study on the potential of using a 3-band spectrometric approach to accurately measure atmospheric CO 2 from space. The OCO-2 mission has adopted the measurement strategy pioneered by their simulation study.…”
Section: XI Et Al: Simulated Retrievals From Geostationary Orbitmentioning
confidence: 99%
See 1 more Smart Citation
“…to detect small geographic and temporal changes. The usefulness of the 0 2 A-band in improving spaceborne C02 measurements, however, is predicated on accurate simulation of its absorption spectrum [9].…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated by Kuang et al (Kuang et al, 2002) and D. Crisp et al (Crisp et al, 2004), three bands in the visual and nearinfrared solar-reflected spectra are required to accurately measure atmospheric CO 2 and to efficiently eliminate the impacts of aerosols and clouds (Cressie et al, 2016). Table 1 shows a summary of the ACGS spectral requirements, including the spectral ranges and resolutions.…”
Section: Spectral Performance Requirementsmentioning
confidence: 99%